Addressing gaps in physician knowledge regarding transgender health and healthcare through medical education - McPhail, Deborah; Rountree-James, Marina; Whetter, Ian (Revue canadienne de l'éducation médicale, 2016)
Background: Transgender people (those people whose sex at birth does not “match” their felt gender identity) are a priority group for healthcare as they experience high rates of discrimination and related illnesses. Despite this, there is a trend of poor healthcare access for trans people due, in large part, to the denial of care on the part of physicians. A small body of literature is beginning to suggest that this denial of care may be due to a lack of physician knowledge as well as, in some cases, to transphobia. There is a dearth of research in Canada, however, exploring whether and/or how knowledge gaps create barriers to quality care, and whether medical education can attend to these gaps while and through addressing gender normativity. Methods: To fill these gaps in the literature, we undertook a qualitative study with 30 trans identified people and 11 physicians (N=41) in Winnipeg, Manitoba. Methods included semi-structured individual interviews and focus groups. Data were transcribed and analyzed with NVivo qualitative data software using iterative methods. Results: An overwhelming finding of this study was a lack of physician knowledge, as reported both by trans people and by physicians, that resulted in a denial of trans-specific care and also impacted general care. Transphobia was also identified as a barrier to quality care by both trans people and physicians. Physicians were open to learning more about trans health and healthcare. Conclusions: The findings suggest a pressing need for better medical education that exposes students to basic skills in trans health so that they can become competent in providing care to trans people. This learning must take place alongside anti-transphobia education. Based on these findings, we suggest key recommendations at the close of the paper for providing quality trans health curriculum in medical education.